Comparison of disposable sutureless silicone ring and traditional metal ring in 23-gauge vitrectomy combined with cataract surgery - Li X-R (Dove Medical Press, 2011)
Jian-Guo Wu, Rui-Hua Wei, Ai-Hua Liu, Xiao-Xu Zhou, Guo-Ling Sun, Xiao-Rong LiTianjin Medical University Eye Center, Tianjin, ChinaBackground: The purpose of this prospective, interventional, comparative case series was to evaluate the efficiency and feasibility of a disposable sutureless silicone lens ring for corneal contact lens stabilization during combined 23-gauge vitrectomy and cataract surgery.Methods: We developed a ring consisting of a single silicone component with three footplates along the ring margin to fit cannulae for holding conventional contact lenses. Thirty eyes from 30 patients with cataract and vitreoretinal disease were included, and divided into two matched groups according to disease type and ring used. In Group A, we used a 23-gauge transconjunctival vitrectomy system and a disposable sutureless silicone lens ring (n = 15). In Group B, we used a 23-gauge transconjunctival vitrectomy system and a conventional metal lens ring (n = 15). The main outcome measures were: time required for vitrectomy preparation, rate of intraoperative corneal limbus bleeding, and limbus scar rate at the final follow-up visit.Results: Thirty cases were successfully completed. The average vitrectomy preparation time was less in Group A than in Group B (P < 0.01), and the average preparation time saved was 3.94 minutes. None of the Group A patients had intraoperative bleeding or postoperative scarring, whereas all 15 Group B cases had bleeding and five had scarring. There was a statistically significant difference between Group A and Group B for these complications (P ≤ 0.05).Conclusion: This report demonstrates the advantages of using a sutureless silicone ring during combined 23-gauge vitrectomy and cataract surgery. Using this method could allow extra time for the surgeon to pay more attention to complex vitreoretinal procedures.Keywords: pars plana vitrectomy, contact lens, silicone ring, cataract surgery